GLOBAL RAILWAY CONSTRUCTION IN THE 19th CENTURY: MAIN DIRECTIONS AND TRENDS - Xolliyev A. G. (TARIXIY TADQIQOTLAR, 2026)
This article, based on a wide range of factual material, examines from a historical perspective the main directions and trends in the multifaceted development of global railway construction in the 19th century. The primary focus is on a comprehensive analysis of the place and role of railways in the overall development of numerous countries, as well as an investigation of the relationship between the large-scale growth of railway networks and the international situation, technical and social evolution of various regions of the world.